Adaptasi Media Sosial oleh Organisasi Keagamaan di Indonesia: Studi Kanal YouTube Nahdlatul Ulama, NU Channel - Setia, Paelani; Iqbal, Asep Muhamad (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article discusses how religious organizations use social media by focusing its analysis on Nahdlatul Ulama and its YouTube channel, NU Channel. Using a qualitative method, this study collected its required data through online observation of NU Channel. This article argues that the assumption that Nahdlatul Ulama is a religious organization that tends to be traditionalist and conservative towards technological developments is incorrect. Nahdlatul Ulama is willing to adopt the internet as a new medium for conveying its religious views. The findings show that Nahdlatul Ulama is adaptive to social media as seen its adoption of YouTube as a new medium of religious studies conducted online on NU Channel. All this show a digital transformation within Nahdlatul Ulama’ religious studies, which is traditionally identical with pesantren, direct learning method with kiai, and other conventional ways of education and learning.